Morpho - adaptation anatomy of sweet gourd Momordica cochinchinensis (Lour.) Spreng. grown in Sa Pa, Lao Cai and Cuc Phuong, Ninh Binh - Lan Huong, Do Thi; Ba, Tran Van (Academia Journal of Biology, 2012)
Based on morphological characteristics and structural adaptation anatomy of sweet gourd Momordica cochinchinensis, grown in the Cuc Phuong national park and Sa Pa town, we found that stem of sweet gourd is a small vine with cirri which wraps directly around a cultivating medium. Vascular bundle system is not formed a closed loop in the trunk, however the stem has flexible structure as a result of the intercellular spaces are widen between the bundles. M. cochinchinensis is a light preferable crop with a thick-layed cuticle and numerous stomata, palisade tissues and spongy tissues are rich in layers. Two cultivars of sweet gourd collected from two research sites with different elevations that result differences of mophogical and anatomical characteristics of M. cochinchinensis in geographical positions which are quite different and based on observations and experiments, some differences in both morphology and anatomy of sweet gourd have been discovered.